Standards of Adolescent Civilized Communication on Social Media - Siahaan, Chontina; Adrian, Donal (Jurnal Komunikasi dan Bisnis, 2024)
The current millennial generation uses more trending sentences to follow but is uncivilized. This is due to the enormous influence of the development of communication technology, namely the internet, and applied through the use of social media. The purpose of this study is to find out and explain the standards of civilized communication among adolescents on social media. Using qualitative research methods, inductive and constructivist paradigms, as well as collecting data through the field and virtual observations and in-depth interviews to produce valid research results. The results showed that civilized communication standards practiced by high school students in Jakarta were (a) answering questions quite briefly even though they interacted with parents, not giving forms of appreciation with the words mama or papa, (b) avoiding meeting other people face to face and prefer to use smartphones to communicate online, and (c) self-existence by uploading any kind of information on social media accounts and disseminating it.